Amazighité et contestations au Maroc - Ibrahimi, Abdennacer El (Studies in the History and Society of the Maghrib, 2022)
Résultat d'un long travail de terrain, ce livre analyse les processus d'émergence du mouvement amazigh au Maroc et les dynamiques protestataires qui ont accompagné son évolution, des années 1960 à nos jours. En plaçant au centre de l'étude les transformations du phénomène protestataire au Maroc, il apporte un éclairage à la fois fascinant et inédit sur la question amazighe, ses causes, ses acteurs et ses formes, puis sur les enjeux identitaires portés par le mouvement amazigh dans la redéfinition de l'État-nation au Maroc. This book, which represents the fruit of an extended field research, analyses the birth process of the Amazigh movement in Morocco and explores the dynamics of protests that have accompanied its growth from the 1960's until today. Centred around the transformation of protests over time, this book introduces fresh and fascinating insights into the Amazigh question, its causes, its actors and the various shapes it has taken over the years, and sheds new light on the compelling identity issues that were raised by the Amazigh movement throughout Morocco's redefinition of the Nation-State model.